Skrining Fitokimia dan Aktivitas Antioksidan Ekstrak Daun Benalu Jeruk (Dendrophthoe glabrescens (Blakely) Barlow) dengan Pelarut n-Heksan dan Etanol - Udayani, Ni Nyoman Wahyu; Wiguna, Putu Dony Saputra; Cahyaningsih, Erna; Wardani, I Gusti Agung Ayu Kusuma (Jurnal Ilmiah Medicamento, 2023)
One of the compounds that can be exploited from plants is antioxidants. Antioxidants are compounds that are important in overcoming free radicals in the body. Natural antioxidants are more desirable than synthetic ones because of their minimal side effects. Mistletoe is a parasitic plant that has been used in traditional medicine in Indonesia. This study aims to determine the content of secondary metabolites contained in citrus parasite leaf extracts using non-polar and polar solvents and how their antioxidant activity is. with a ratio of material and solvent 1:10. The screening tested included alkaloids, triterpenoids, steroids, flavonoids, saponins, and tannins. The method used to test the antioxidant activity of the orange parasite leaf extract is the DPPH method as measured by a UV-Vis spectrophotometer. Statistical analysis was carried out using One Way Anova and Post Hoc on the IC50 value of the extract with a 95% level of confidence. From the results of research conducted, the N-Hexane extract of citrus parasite leaves contained secondary metabolites of alkaloids, steroids and flavonoids, and the ethanol extract of orange parasite leaves contained secondary metabolites of alkaloids, steroids, flavonoids, saponins, and tannins. The antioxidant activity of the n-Hexane and ethanol extracts were 92.731 ppm (strong) and 54.490 ppm (strong) respectively.